Faktor-faktor yang Mempengaruhi Jumlah Kelahiran di Provinsi Sumatera Barat dengan Menggunakan Analisis Faktor - Resti Febrina; Nonong Amalita; Dewi Murni (Journal of Mathematics UNP, 2014)
Abstract –– The Problem of birth is one of the unresolved issues in West Sumatra. The birth rate in western Sumatra in the high category, where a mother gives birth to an average of three to four childrens. Increasing the number of births means that population growth will affect the welfare of society. It required effort to see birth control factors affecting birth. To find out which factors that affect the number of births in the province of West Sumatra is used by factor analysis. Base on the results obtained the data analysis three factors that affect the number of births in the province of West Sumatra that women with low education or undergraduate, women who married at the end of adolescence, and women who are married under-age and use contraceptive.   Keywords –– Factor analysis, Problem of birth, and Number of birth.